Capacidade negativa: a importância do não saber, da espera e do mistério em psicanálise - Ferreira, Lais Nae Yamaguchi (2024)
How important is negative capacity in current clinical practice in psychoanalysis? Coined by psychoanalyst Wilfred Bion based on inspiration from a letter by the poet John Keats, this concept relates to the analyst's ability to deal with not knowing, uncertainties and mysteries. The interest in this research arises as a result of the observation of contemporary symptoms, in which excess, speed, performance and saturation predominate: whether of information, of knowing, of doing. This is a theoretical-clinical research and, based on the clinical case presented, different dimensions and clinical management were explored in light of negative capacity